2007
DOI: 10.1016/j.jemermed.2007.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Adverse Outcomes in Syncope

Abstract: Syncope is a common presentation to the Emergency Department (ED); however, appropriate management and indications for hospitalization remain an ongoing challenge. The objective of this study was to determine if a predefined decision rule could accurately identify patients with syncope likely to have an adverse outcome or critical intervention. A prospective, observational, cohort study was conducted of consecutive ED patients aged 18 years or older presenting with syncope. A clinical decision rule was develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(112 citation statements)
references
References 20 publications
1
108
0
3
Order By: Relevance
“…However, the authors excluded patients with acute identifiable events such as stroke, pneumonia, or myocardial infarction, which renders the algorithm useful only in patients with fall or unknown cause of syncope. The Boston Syncope Criteria was proposed to triage patients with syncope and was shown to have a sensitivity of 97% and specificity of 62% in predicting 30‐day adverse outcomes or critical interventions; however, readmission was not included as an adverse outcome 26. Other models, such as the San Francisco Syncope Rule and Osservatorio Epidemiologico sulla Sincope nel Lazio scores, have been used to risk‐stratify patients for long‐term adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors excluded patients with acute identifiable events such as stroke, pneumonia, or myocardial infarction, which renders the algorithm useful only in patients with fall or unknown cause of syncope. The Boston Syncope Criteria was proposed to triage patients with syncope and was shown to have a sensitivity of 97% and specificity of 62% in predicting 30‐day adverse outcomes or critical interventions; however, readmission was not included as an adverse outcome 26. Other models, such as the San Francisco Syncope Rule and Osservatorio Epidemiologico sulla Sincope nel Lazio scores, have been used to risk‐stratify patients for long‐term adverse outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Examples of such rules are the risk stratification of syncope in the emergency department (Rose), San Francisco Syncope Rule (SFSR), and Boston Syncope Rules, 7,8,15 with the SFSR 8 being the only rules that are externally validated.…”
Section: Rulesmentioning
confidence: 99%
“…15 The investigators recruited 362 patients and considered the variables (risk factors) reported in the American College of Emergency Physicians' clinical policy on syncope. 22 Given the presence of at least 1 of the variables, the sensitivity and specificity of the rule was 97% (95% CI 93-100) and 62% (95% CI 56-69), respectively (see Tables 1-3).…”
Section: The Boston Syncope Rulementioning
confidence: 99%
“…12,13 In recent years, various prediction rules based on the probability of an adverse outcome after an episode of syncope have been proposed. 3,[14][15][16] However, the San Francisco Syncope Rule, derived by Quinn and colleagues in 2004, 3 is the only prediction rule for serious outcomes that has been validated in a variety of populations and settings. This simple, five-step clinical decision rule is intended to identify patients at low risk of short-term serious outcomes 3,17 (Box 1).…”
mentioning
confidence: 99%